Proposing a wiki-based technique for collaborative essay writing (2014)
This paper aims at proposing a technique for students learning English as a foreign language when they collaboratively write an argumentative essay in a wiki environment. A wiki environment and collaborative work play an important role within the academic writing task. Nevertheless, an appropriate and systematic work assignment is required in order to make use of both. In this paper the proposed technique when writing a collaborative essay mainly attempts to provide the most effective way to enhance equal participation among group members by taking as a base computer mediated collaboration. Within this context, the students’ role is clearly defined and individual and collaborative tasks are explained.Este artículo tiene como objetivo proponer una técnica para la escritura colaborativa de un texto académico en inglés como lengua extranjera en un entorno virtual wiki. El entorno virtual y el trabajo colaborativo juegan un papel importante dentro de la tarea de escritura. Sin embargo, se requiere un trabajo sistemático con el fin de articular la metodología colaborativa con la herramienta tecnológica. La propuesta de este artículo intenta proporcionar una técnica de trabajo que propicie la participación equitativa de los miembros del grupo y considere las características del trabajo colaborativo y las del entorno virtual. Dentro de este contexto, el rol del estudiante es claramente definido a través de la división de tareas individuales y colaborativas.